Derivación de valores económicos de la producción de leche de bovinos en la parroquia Aláquez utilizando funciones de beneficio. - Cabascango Criollo, Karla Michelle (2022)
In the parish of Aláquez, Latacunga canton, province of Cotopaxi, a study was conducted on the derivation of economic values of bovine milk production, using profit functions, with the objective of describing the dairy production systems, derive economic values for genetic selection criteria associated with economic utility and define subsequent selection criteria to be used in the genetic improvement program in the long term, this parish is made up of 28 neighborhoods, being a parish of relatively high milk production within the province, the methodology consisted of socializing the project which was accepted in 4 neighborhoods, The methodology consisted of socializing the project, which was accepted in four neighborhoods: Tandaliví, San Antonio, San Marcos and El Tejar, all of which are considered high producers; small and medium producers were reached and a census and data collection was carried out, At the same time, the established parameters were recorded, such as coordinates, size of areas designated for cattle and personal information. As for the cattle, weight, age, frequent diseases, density tests, milk weight and mastitis test were recorded. We obtained 32 partners with 332 heads of cattle, where 69.2% were females of which cows represent 42.9% and are milk producers, 2.5% are wombs, 9% are dry cows, 21.1% are heifers and 4.7% are calves, 1.9% are suckling cows. As for male cattle we obtained 30.8%, where we found that 9.9% are bulls, 5.6% are calves and 2.5% are adult bulls. With the data collected, we were able to determine the costs, benefits and profitability of milk production in order to verify if there are profits according to the size of the area and the investment in it, and with this we were able to establish the selection criteria for the genetic improvement program. We concluded that the production system used in Aláquez is segued and mixed, regarding production costs, it was obtained that producing a liter of milk costs 0.35 cents and the sale price is 0.40 cents, a beneficial result for the producers, the selection criteria were chosen with the shortcomings of the parish which were milk density, days of lactation and nutrition. The technical, economic and social impacts had repercussions on small and medium producers in the parish of Aláquez.